In vitro efficacies of solubility-improved mebendazole derivatives against Echinococcus multilocularis. Issue 10 (6th May 2019) - Xu, Shuo; Duan, Liping; Zhang, Haobing; Xu, Bin; Chen, Junhu; Hu, Wei; Gui, Weifeng; Huang, Fuqiang; Wang, Xu; Dang, Zhisheng; Zhao, Yumin
Abstract: Recently, we introduced an epoxy group to mebendazole by a reaction with epichlorohydrin and obtained two isoforms, mebendazole C1 (M-C1) and mebendazole C2 (M-C2). The in vitro effects of mebendazole derivatives at different concentrations on Echinococcus multilocularis protoscoleces and metacestodes as well as cytotoxicity in rat hepatoma (RH) cells were examined. The results demonstrated that the solubility of the two derivatives was greatly improved compared to mebendazole. The mortality of protoscoleces in vitro reached to 70–80% after 7 days of exposure to mebendazole or M-C2, and M-C2 showed higher parasiticidal effects than mebendazole ( P > 0.05). The parasiticidal effect of M-C1 was low, even at a concentration of 30 µ m . The percentage of damaged metacestodes that were treated with mebendazole and M-C2 in vitro at different concentrations were similar, and M-C1 exhibited insignificant effects on metacestodes. Significant morphological changes on protoscoleces and metacestodes were observed after treatment with mebendazole and M-C2. In addition, the introduction of an epoxy group to mebendazole also reduced its cytotoxicity in RH cells. Our results demonstrate that the introduction of an epoxy group not only improved the solubility of mebendazole, but also increased its parasiticidal effects on E. multilocularis and reduced its cytotoxicity in RH cells.